Kaviśrī Nhānālāla janmaśatādbī smrtigrantha : Gujarāta Yunivarsiṭīnī abhyāsetara pravrttionī yojanā heṭhaḷa kaviśrī Nhānālāla janmaśatābdī samāroha nimitte tā. 27-2-1978 thī tā. 4-3-1978 kaviśrīnā jīvana ane kavana vishe apāyelāṃ vyākhyāno - Raval, Anantrai Manishankar, 1912- (Gujarāta Yunivarsiṭī prakāśana., 1978)
Articles on the life and works of Nanalal Dalpatram Kavi, 1877-1946, Gujarati litterateur; originally delivered as lectures under the auspices of Gujarat University, 1978.